(untitled) (Research, Society and Development, 2020)
The edaphic macrofauna includes several organisms that play an important role in the cycling of nutrients and improvements in the chemical and physical properties of the soil. These organisms are used as bioindicators of the functioning of ecosystems. Aiming at such factors, the objective was to evaluate the population diversity of edaphic organisms in areas with different cultivated pastures. The experiment was carried out in the forest area of Alagoas, in the municipality of Coruripe, Alagoas. The study was carried out on four pastures cultivated with Mombasa (Panicum maximum), Tifton 85 (Cynodon spp.), Brachiaria humidicola and Brachiaria Brizantha with an area of 100m² each. Twenty Provid traps were used per pasture. After 96 hours of installation of the traps, the organisms were quantified, identified and grouped according to the order and / or taxonomic group. After data analysis, it was observed that the area occupied with B. Brizantha grass had the greatest diversity, being followed by the areas with Mombasa and tifton 85. The area with the least diversity was that occupied with B. humidicola pasture. The order Aranae was present in all areas, with representation above 3.85 of the individuals found. All pastures presented a greater representation of the order Hymenoptera. Coleopteras showed a denser (2.60) and dominant (0.23) population in the mombaça pasture. The edaphic fauna is subject to change according to the change in the vegetation used to form the pasture.